The Effect of Aging on the Accuracy of Spring-Style Mechanical Torque Limiting Devices for Dental Implants - Sadr, Jalil; Fayyaz, Ali; Mahshid, Minoo; Saboury, Abolfazl (Journal of Dental School, 2020)
Objective: Recently, a wide variation has been reported in delivery of the target torque by spring- style mechanical torque limiting devices (MTLDs) but the effect of aging on their accuracy has not been independently evaluated. The purpose of this study was to determine the effect of aging on the accuracy of spring-style MTLDs. Methods: In this in-vitro experimental study, 15 new spring-style MTLDs were selected of three different manufacturers. To measure their accuracy, the peak torque was measured in 10 sequences by a Tohnichi torque gauge before and after 1000 times of use. In each sequence, 10 repetitions of peak torque values were registered. The intra-class correlation coefficient (ICC) was calculated and Repeated Measures ANOVA and two-way ANOVA were applied to calculate and compare the absolute error values between the three understudy groups. Results: The absolute error value was in the range of -3.5(-3) Ncm for 3i group, -2.5 (1) Ncm for ITI and -4-+2 Ncm for Nobel Biocare group. The latter value showed a significant difference with the two former values (p<0.05). All samples in the ITI group had error values within 10% of the clinically acceptable range. About 5% of measurements (maximum of 11.4%) in Nobel Biocare and 9% of measurements (maximum of 14.53%) in the 3i group showed error values greater than the 10% range. Conclusion: Aging decreased the accuracy of spring-style MTLDs. The magnitude and trend of reduction in accuracy were variable among different groups.